The Challenging of Medical Rehabilitation - Irma Ruslina Defi (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Rehabilitation aims to enhance and restore functional ability and quality of life from the variety of medical conditions experiences or likely experience disability. The function status associated with physical activity is a health indicator. Human functioning is a major target of the rehabilitation program.